Pencegahan Pernikahan Dini Melalui Penyuluhan Pendidikan Agama Islam (PAI) di Desa Tano Bato Kec. Barumun, Kab. Padang Lawas - Elida Mantapia Nst; Zainal Efendi Hsb (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Early marriage has become a serious concern in the village of Tano Bato, Kecamatan Barumun, Kabupaten Padang Lawas. This research proposes the implementation of an Islamic Religious Education (PAI) outreach program as a strategy to prevent early marriages in the region. The outreach method involves collaboration with religious figures, educators, and the local community to deliver in-depth information on Islamic values related to marriage, responsibilities, and the negative impacts of early marriages. The primary goal of this program is to enhance the understanding of the community, especially teenagers, regarding Islamic religious laws related to marriage and to provide a holistic perspective on physical and mental readiness for family life. Program evaluation is conducted through interviews, questionnaires, and impact monitoring to measure its effectiveness. This community service provides a concrete overview of efforts to prevent early marriages through Islamic Religious Education outreach in the village of Tano Bato as a commitment to religious values and the well-being of the local community.